Tourism SMEs in a Digital Environment: Literature Review - Juan Carlos Bocarando Lara; Juan Carlos Pérez García; Catalina Ovando Chico (European Scientific Journal, ESJ, 2017)
Purpose - The aim of the research is to present the main challenges faced by Small and Medium Enterprises (SMEs) in the tourism industry, to build and enhance their value proposition within the framework of a digital environment. Design/methodology/approach - The authors carried out a review of the literature in databases using keywords. The selection of sources includes scientific articles and case studies based on different methods and contexts. Findings - The findings suggest that in a context characterized by the integration of the economy and the interference of Information and Communication Technologies (ICT), commercialization has become flexible and accessible. The above has had a tangible impact on the structure of the market and in the way in which the SMEs in the tourism industry are managed. Research limitations/implications - The study offers an up-to-date and global vision for future researchers through the review of the literature on SMEs located in the tourism industry in the context of a digital environment. Social implications - The study shows that to survive and grow, SMEs in the tourism sector must differentiate themselves from their competitors, evolve in their business model and rapidly integrate ICT in their organizational fabric. Originality/value - The construction of a value proposition for SMEs in the tourism sector should be settled on an understanding of the position held, on the competence of the competitors and the needs of the market.